(untitled) (Journal of the College of Basic Education, 2022)
This study aims to evaluate the effectiveness of different GnRH and PGF2α hormonal treatments on Iraqi river buffaloes producing milk (Bubalus bubalis) endemic in the south of Baghdad and suffering from polycystic ovaries for more than 4-8 months. The study’s 93 animals were divided into two groups, the first group contained 43 animals that were treated with GnRH hormone, while the second group included 50 animals treated with a mixture of GnRH and PGF2α hormones.Fertility and pregnancy were calculated after 60-90 days of treatment and were found to be 69.7% and 78.8% in the first and second groups, respectively. There were no significant differences (P < 0.05) between the two groups. The treatment of the second group proved to be superior to treatment compared to the first group in improving the pregnancy rate.Keywords: polycystic ovaries, buffalo cows, GnRH, PGF2α.